2021
DOI: 10.1186/s13018-021-02838-z
|View full text |Cite
|
Sign up to set email alerts
|

First dorsal metacarpal artery flap with dorsal digital nerve with or without dorsal branch of the proper digital nerve produces comparable short-term sensory outcomes

Abstract: Background The first dorsal metacarpal artery flap, including dorsal digital nerves with or without dorsal branches of the proper digital nerves, can be used to reconstruct thumb pulp defects with good results. However, it is still unclear whether there are differences in the sensory outcomes between preserving or not preserving the dorsal branches of the proper digital nerves. Methods This retrospective cohort study included 137 thumb pulp defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Both the dorsal digital nerve and the dorsal branches of the proper digital nerve were commonly used in island flap to cover the finger defects. Han et al 7 reported that if the dorsal digital nerves were carried in the flap, preserving the dorsal branches of the proper digital nerve had no obvious clinical advantages in the restoration of sensation. Although they can repair finger pulp defects for 1-stage procedure and achieve good sensory recovery, there are several shortcomings, such as noticeable donor-site scarring, hair carrying, and sensory loss on the dorsal side of the finger 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the dorsal digital nerve and the dorsal branches of the proper digital nerve were commonly used in island flap to cover the finger defects. Han et al 7 reported that if the dorsal digital nerves were carried in the flap, preserving the dorsal branches of the proper digital nerve had no obvious clinical advantages in the restoration of sensation. Although they can repair finger pulp defects for 1-stage procedure and achieve good sensory recovery, there are several shortcomings, such as noticeable donor-site scarring, hair carrying, and sensory loss on the dorsal side of the finger 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to preserve the nerve supply of the flap to have good sensation postoperatively. 7,23,30,[32][33][34][35] There is no definite answer regarding which nerve to select when performing the reverse digital artery island flap procedure. Both the dorsal digital nerve and the dorsal branches of the proper digital nerve were commonly used in island flap to cover the finger defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the complex innervation of the index, middle, ring, and little fingers, the origin and distribution of the dorsal digital nerves of the thumb are constant and the diameter of the nerves is larger. A recent retrospective cohort study showed that coaptation of the dorsal digital nerves originated from SBRN with the PPDN in the thumb pulp defect was superior to non-coaptation in sensory recovery [ 17 ]. The discrepancy between the results of the above study and ours may be due to the differences in the dorsal nerves of the thumb and other fingers.…”
Section: Discussionmentioning
confidence: 99%